Keamanan Online dalam Media Sosial: Pentingnya Perlindungan Data Pribadi di Era Digital (Studi Kasus Desa Pematang Jering) - Putri, Adelia; Sari, Nilam; Fajrina, Putri; Aisyah, Siti (Lembaga Penelitian dan Pengabdian Kepada Masyarakat (LPPM) STMIK Indonesia Banda Aceh, 2025)
Urgency of protecting personal data in the use of social media in the digital era, with a case study of Pematang Jering Village. Amidst rampant cyber crimes such as hacking and identity theft, this rural community faces significant challenges due to a lack of understanding about digital security. This research emphasizes the importance of digital literacy and awareness of the risks lurking in users' personal data on social media. The study uses a qualitative methodology with an ethnographic approach, involving in-depth interviews with village residents, including victims of hacking and cybersecurity experts, as well as participatory observation for one month to understand the dynamics of social media use and the community's awareness level regarding data security. Data was also collected through document analysis related to data protection policies. The findings reveal that the majority of respondents have a low understanding of digital security risks despite their active use of social media in daily life. The lack of digital literacy leaves village residents vulnerable to cyber crimes; some have experienced incidents such as identity theft or misuse of personal data. The research identifies the absence of local regulations and security infrastructure as aggravating factors for this vulnerability. In conclusion, there is an urgent need to enhance digital literacy among rural communities, particularly through educational interventions that engage the youth as agents of change. The practical implications of this study include recommendations for the development of structured digital education programs and the implementation of stronger regulations and adequate security infrastructure to safeguard personal data. A holistic approach is needed to create a safe and sustainable digital ecosystem at the community level.